# How do you simplify -a * -a?

Mar 16, 2017

$\left(- a\right) \cdot \left(- a\right) = \textcolor{g r e e n}{{a}^{2}}$

#### Explanation:

$\left(- a\right) \cdot \left(- a\right) \textcolor{w h i t e}{\text{XXX}}$I've added the parentheses
$\textcolor{w h i t e}{\text{XXXXXXXXXXX}}$since having multiple operators in a row can be confusing.

$\textcolor{w h i t e}{\text{XXX}} = \left(- 1\right) \cdot a \cdot \left(- 1\right) \cdot a$

$\textcolor{w h i t e}{\text{XXX}} = \left(- 1\right) \cdot \left(- 1\right) \cdot a \cdot a$

$\textcolor{w h i t e}{\text{XXX}} = + 1 \cdot {a}^{2}$

$\textcolor{w h i t e}{\text{XXX}} = {a}^{2}$

Mar 16, 2017

See the entire simplification process below:

#### Explanation:

Use these two rules of exponents to simplify this expression:

$a = {a}^{\textcolor{red}{1}}$ and ${x}^{\textcolor{red}{a}} \times {x}^{\textcolor{b l u e}{b}} = {x}^{\textcolor{red}{a} + \textcolor{b l u e}{b}}$

$- a \cdot - a = - {a}^{\textcolor{red}{1}} \cdot - {a}^{\textcolor{b l u e}{1}} = {\left(- a\right)}^{\textcolor{red}{1} + \textcolor{b l u e}{1}} = {\left(- a\right)}^{2}$